Successful Steroid Therapy of Henoch Schonlein Purpura in Young Adult Woman with Moderate Symptoms: A Case Report - Yafanita Izzati Nurina; Awalia; Fariska Zata Aman; Nanda Aulya Ramadhan (Indian Journal of Forensic Medicine & Toxicology, 2021)
Henoch schonlein purpura is a rare incidence case and almost similar to the clinical symptoms of autoimmunediseases such as systemic lupus erythematus in young adult woman. A 23-year old woman patient presentedwith reddish spots accompanied by a burning sensation and pain in both legs, vomiting profus and abdominalpain. She also complained mild fever, frequent mouth sores, hair loss, joint pain and stiffness, frequentfatigue in the last 1 month. Laboratory tests showed mild anemia, leukocytocis, proteinuria, erythrocytes andleukocytes microscopic in urinalysis, increased of serum IgA and LED. The skin biopsy showed neutrophilcell infiltration in the capillary vessel walls with necrotic debris. Methylprednisolone oral was given since shehospitalized and decreased gradually. This case hada good prognosis because the result of serum creatininewas normal insix months latereven though had moderate symptoms.